Ranitidine Inhibition of Breast Tumor Growth Is B Cell Dependent and Associated With an Enhanced Antitumor Antibody Response - Rogers, Dakota; Vila-Leahey, Ava; Pessôa, Ana Clara; Oldford, Sharon; Marignani, Paola A.; Marshall, Jean S. (Frontiers in Immunology, 2018)
Background: The histamine receptor 2 antagonist ranitidine is a commonly used, non-prescription, medication. It limits the development, growth and metastasis of breast cancers in mouse models of disease. In the current study, we examined the role of B cells in this response, the impact of ranitidine on the development of anti-tumor antibodies and subpopulations of natural killer cells using murine breast cancer models. Methods: Peripheral blood granulocyte populations were assessed in both E0771-GFP and 4T1 orthotopic tumor bearing mice by evaluation of stained blood smears. Antibody responses were assessed both in terms of the levels of anti-GFP antibodies detected by ELISA and also by antibody binding to the surface of tumor cells evaluated by flow cytometry. B cell and NK cell populations were examined in the draining lymph nodes and spleens of tumor bearing animals, by flow cytometry with and without ranitidine treatment. Results: Oral ranitidine treatment was not associated with changes in peripheral blood granulocyte populations in tumor-bearing mice. However, ranitidine treatment was associated with the development of enhanced anti-tumor antibody responses. This was not limited to the tumor setting since ranitidine treated mice immunized with ovalbumin also demonstrated increased IgG antibody responses. Analysis of B cell populations indicated that while B1 cell populations remained unchanged there was a significant decrease in B2 cells in the tumor draining inguinal lymph nodes. Notably, ranitidine did not significantly inhibit primary tumor growth in B cell-deficient animals. Examination of NK cell populations revealed a significant decrease in the proportion of intermediately functionally mature NK cells populations (CD27+CD11b-in ranitidine-treated tumor bearing mice compared with untreated tumor bearing controls. Conclusions: These data demonstrate an important role for B cells in the enhanced anti-tumor immune response that occurs in response to ranitidine treatment. Our findings are consistent with a model whereby ranitidine reduces tumor associated immune suppression allowing for the development of more effective anti-tumor responses mediated by B cells which may include the participation of NK cells. These data underline the importance of considering widely used histamine receptor antagonists as modulators of anti-tumor immunity to breast cancer.